The North Carolina Way: emerging healthcare system and faith community partnerships. Issue 5 (4th July 2017) - Cutts, Teresa; Gunderson, Gary
ABSTRACT: United States healthcare policy has promoted the development of healthcare systems and community partnerships designed to decrease costs and readmissions, particularly for under-served populations. Typically, these partnerships are "hospital-centric", focused on following in-house clinical costs into the community. Two contrasting large-scale community system models show results from development practices, integrating faith community partnerships that affect healthcare utilisation. This "community to hospital" focus is key to several such initiatives in the US. This article describes local implementation efforts in North Carolina, known as "the North Carolina Way", and tests assumptions on implementation practices for creating robust faith-community and healthcare partnerships.